(untitled) (Research, Society and Development, 2023)
Introduction: Leprosy is a chronic infection caused by Mycobacterium leprae, primarily affecting the peripheral nerves. It is known that despite the reduction in the number of new cases, transmission remains active due to the incidence of cases in children under 15 years of age. Thus, the search for more sensitive and specific diagnostic methods for the detection of subclinical infection becomes relevant. Objective: to verify, through qPCR, the presence of M. leprae in intradermal scrapings (IS) of individuals treated at CREDEN-PES/GV/MG. Method: Intradermal scraping (IS) samples were collected from 411 participants to determine the bacilloscopic index (BI), extraction, and amplification of M. leprae DNA. Participants were divided into two groups: GROUP 1, “Notified cases,” registered at SINAN; GROUP 2, “Individuals not notified,” who had a suspected diagnosis of leprosy. Of the total of 411 samples collected, 158 were obtained from notified cases and 253 from not notified individuals. Results: It was found that of the total number of cases, 58.86% (male) and 41.14% (female). Among the not notified individuals, 53.36% (male) and 46.64% (female). Considering the age range, both groups were aged (40 to 69 years). As for the IS, 34.18% (cases) and 0% (not notified) had a positive IS. In qPCR, 82.28% of cases and 47.43% of not notified individuals tested positive, with an illness odds ratio of 5.14. Conclusion: It is possible to infer those individuals with suspected leprosy, with positive qPCR, may be carriers of subclinical infection and potential transmitters of M. leprae to more susceptible individuals.